(untitled) (Journal of Additive Manufacturing Technologies, 2022)
Wire + Arc Additive Manufacturing (WAAM) is relatively a novel manufacturing technology which uses metallic wire as the feedstock material and normal arc as the heat source to build up large scale near-net-shape parts. This process has attracted the attention of many industries such as aerospace, defense and automotive due to its ability to produce very near-net-shape components without complex tooling and molds offers potential for significant cost and lead time reductions. In this paper, the mechanical and metallurgical properties of the WAAM ER70S-6 are studied during tension loading as well as microhardness testing and its behavior is correlated with microstructural observations. The microstructure of WAAM ER70S-6 is assessed by optical microscopy (OM). The results show that the selected parameters for deposition of ER70S-6, leads to an isotropic mechanical behavior during tension loading. The microhardness level is not changing in different regions of WAAM-fabricated ER70S-6, confirming presence of relatively homogenous microstructure.